2023
DOI: 10.3390/s23136090
|View full text |Cite
|
Sign up to set email alerts
|

FMDNet: An Efficient System for Face Mask Detection Based on Lightweight Model during COVID-19 Pandemic in Public Areas

Abstract: A new artificial intelligence-based approach is proposed by developing a deep learning (DL) model for identifying the people who violate the face mask protocol in public places. To achieve this goal, a private dataset was created, including different face images with and without masks. The proposed model was trained to detect face masks from real-time surveillance videos. The proposed face mask detection (FMDNet) model achieved a promising detection of 99.0% in terms of accuracy for identifying violations (no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Additionally, we used the AB, NB, and DT machine-learning classifiers with cross-validation (CV) 5-fold, 10-fold, and leave-one-out models. The mathematical expression for the precision, F1, accuracy, recall, and specificity ( Ullah et al, 2022b ; 2022a ; Sultana et al, 2022a ; Ayalew et al, 2022 ; Nawabi et al, 2022 ; Said et al, 2022 ; Benifa et al, 2023 ; Pal et al, 2023 ; Qadri et al, 2023 ) are shown in Equations 8 - 12 below: …”
Section: Resultsmentioning
confidence: 99%
“…Additionally, we used the AB, NB, and DT machine-learning classifiers with cross-validation (CV) 5-fold, 10-fold, and leave-one-out models. The mathematical expression for the precision, F1, accuracy, recall, and specificity ( Ullah et al, 2022b ; 2022a ; Sultana et al, 2022a ; Ayalew et al, 2022 ; Nawabi et al, 2022 ; Said et al, 2022 ; Benifa et al, 2023 ; Pal et al, 2023 ; Qadri et al, 2023 ) are shown in Equations 8 - 12 below: …”
Section: Resultsmentioning
confidence: 99%
“…Tan [1], Yao [2], Gao [3], and Zhang [4] conducted studies from the perspective of emergency management after the occurrence of a major emergency. Other scholars have investigated the impact of major emergencies, such as Ukwuoma [5], Benifa [6], Asif [7], and Fazmiya [8], who analyzed the physical effects of major emergencies on humans from a medical perspective, using COVID-19 as an example. Mo et al [9] argued that major emergencies have both an emotional as impact as well as a huge economic impact.…”
Section: Related Workmentioning
confidence: 99%
“…This study intended to compare the efficacy of the formulation prepared with acacia gum ( Gond Babul ) and camphor ( Kafoor ) vaginal suppository with tranexamic acid on the pictorial blood loss assessment score (PBLAC), health-related quality of life (HRQoL), and hemoglobin levels in human participants with HMB. The research question was “whether acacia gum and camphor vaginal suppositories would be efficacious to reduce HMB and, thereby, improve the participant’s HRQoL.” Beyond conventional methods, artificial intelligence (AI) ( Benifa et al, 2023 ), particularly machine learning models, was utilized to classify experimental and standard groups. Additionally, this study used experimental data related to heavy menstrual bleeding for the classification of the vaginal suppository group (SG) as an experimental group and tranexamic group (TG) as a standard control group.…”
Section: Introductionmentioning
confidence: 99%
“…The research question was "whether acacia gum and camphor vaginal suppositories would be efficacious to reduce HMB and, thereby, improve the participant's HRQoL." Beyond conventional methods, artificial intelligence (AI) (Benifa et al, 2023), particularly machine learning models, was utilized to classify experimental and standard groups. Additionally, this study used experimental data related to heavy menstrual bleeding for the classification of the vaginal suppository group (SG) as an experimental group and tranexamic group (TG) as a standard control group.…”
Section: Introductionmentioning
confidence: 99%